Effects of Organic Matter from Paitan (Tithonia diversifolia) on the Growth Performance of Arabica Coffee (Coffea arabica) Seedlings in Ultisols - Ridwan; Fathurrahman; Bunga Elim Somba; Muslimin; Abdul Rahim Saleh (Jurnal Penelitian Pendidikan IPA, 2025)
Arabica coffee seedlings grown on Ultisols often experience limited growth due to low levels of organic matter and nutrient deficiencies, presenting a major challenge for nursery productivity in Central Sulawesi. This study aimed to evaluate the effectiveness of organic matter derived from Paitan (Tithonia diversifolia) in improving the growth performance of Coffea arabica seedlings. A Completely Randomized Design (CRD) was employed using five compost dosages (0, 5, 10, 15, and 20 tons/ha equivalent) with four replications. Growth parameters—including germination time, plant height, stem girth, leaf number, leaf area, biomass accumulation, and relative growth rate—were observed over 17 weeks. Soil chemical properties were analyzed to assess changes in fertility. Data were processed using ANOVA followed by an HSD test at the 5% significance level. The results showed that compost substantially improved plant height, stem diameter, leaf number, shoot and root dry weight, and relative growth rate, while germination time, leaf area, and root length remained unaffected. Soil analysis indicated increases in organic carbon, nitrogen, potassium, and cation exchange capacity, demonstrating enhanced nutrient availability. The study concludes that Paitan compost, particularly at 13–15 g per polybag, is an effective organic amendment that improves seedling vigor and offers a sustainable alternative to chemical fertilizers for nursery management on Ultisols.